Pengaruh Metode Isolasi a-mangostin dari Kulit Buah Manggis (Garcinia mangostana L.) terhadap Rendemen α-mangostin - Sri Idawati; Aliefman Hakim; Yayuk Andayani (Jurnal Penelitian Pendidikan IPA, 2019)
Abstract: The purpose of this research is to know the effect of the isolation method of the yield of α-mangostin resulting from mangosteen rind. Mangosteen (Garcinia mangostana L.) is the source of xanthone secondary metabolites. Derivatives xanthone which is the main bioactive compound and becomes a major compound in the mangosteen plant, namely α-mangostin. This main compound has been isolated from ethanol extract on mangosteen rind using different extraction methods namely maceration and soxhletation. Purification was done by the recrystallization method with solvent ethanol: aquades (1:1). The Maceration extraction method produce the yields of extract and the yields of pure compounds (α-mangostin) is higher than that of soxhletation. The Maceration extraction method produces yields of extract 30,12% and yields of α-mangostin 4,27% while the soxhletation extraction method produce the yields of extract 26,34% and the yields of α-mangostin 2,13%. This yellow powder isolate has a melting point of 179,7 ºC. Purification is monitored by thin layer chromatography (TLC) and structural elucidation is carried out using FT-IR spectroscopy data. Key Words: Isolation, α-mangostin, Garcinia mangostana